Contributions to the study of the genus Mongolojassus Zakhvatkin, 1953 (Homoptera: Cicadellidae: Deltocephalinae: Paralimnini) with description of a new species from Northern Caucasus - Tishechkin, Dmitri Yu. (Zootaxa, 2022)
Mongolojassus caucasicus sp. n. from the alpine zone of Dagestan, Northern Caucasus is described, new data on distribution and illustrated descriptions of M. bicuspidatus (J. Sahlberg, 1871) and M. vinokurovi Emelyanov, 1976 are provided. Information on the type series of M. elpatjevskii (Zakhvatkin, 1953) is given. Ecological preferences and distribution patterns of species of Mongolojassus are discussed.